PERSEPSI MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING TERHADAP GUIDED IMAGERY AND MUSIC–PASSIVE MUSIC THERAPY - David Clement R. Batlayar; Dominikus David Biondi Situmorang (Psiko-Edukasi, 2021)
Perception is received by an understanding of the stimulus by the sense organs and enters the brain. Types of perception include sense perception: sight, smell, taste, and sight. There are three factors that influence perception, namely factors: internal, external, and attention. Guided Imagery and Music (GIM) is a method used to assist the counselee in exploring themselves by performing guided imagery, accompanied by using classical musical instruments. The research objective was to determine the perceptions of students towards GIM in the art counseling course. This research is descriptive using an attitude scale instrument. The research subjects were 35 students of the Department of Guidance and Counseling class 2016 and 2017. It shows that students have a perception that is in a positive classification, namely 65.71%, which consists of 23 students from a total of 35 respondents.